DEVELOPMENT OF EMBEDDED SYSTEMS AND INTERNET OF THINGS (IOT) TRAINING KIT (IOT32) - Noval Dwi Jayanto, - (2021)
The COVID-19 pandemic had a significant impact on various sectors, for example, education sector. Due to the outbreak, teaching and learning activities should be carried out online. It becomes a problem in the practical course. This research discusses the development of IoT32 training kit that can be accessed remotely as Learning Media in Embedded Systems and IoT courses. It implements the ADDIE model (Analyze, Design, Develop, Implement, Evaluation). This research measures participants response after using the IoT32 training kit. The research can be concluded that the IoT32 examination showed that IoT32 is proper to be used for IoT practical work. The results also showed that the participants gave a positive response to the IoT32.